2020
DOI: 10.1101/2020.12.03.20242065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival analysis in breast cancer using proteomic data from four independent datasets

Abstract: Breast cancer clinical treatment selection is based on the immunohistochemical determination of four proteins: ESR1, PGR, HER2, and MKI67. Our aim was to correlate immunohistochemical results to proteome-level technologies in measuring the expression of these markers. We also aimed to integrate available proteome-level breast cancer datasets to identify and validate new prognostic biomarker candidates.We identified protein studies involving breast cancer patient cohorts with published survival and proteomic in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus, USP5 is highly expressed in breast tumors and contributes to HIF2α abundance. Moreover, analysis by Kaplan−Meier plotter (https://kmplot.com/analysis) (Ősz et al, 2021), an online survival analysis tool, showed that the high levels of USP5 protein led to the poor clinical overall survival of patients with breast cancer. These results indicate that the protein levels of USP5 are positively correlated with HIF2α protein levels in breast cancer and are associated with poor clinical outcomes in patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, USP5 is highly expressed in breast tumors and contributes to HIF2α abundance. Moreover, analysis by Kaplan−Meier plotter (https://kmplot.com/analysis) (Ősz et al, 2021), an online survival analysis tool, showed that the high levels of USP5 protein led to the poor clinical overall survival of patients with breast cancer. These results indicate that the protein levels of USP5 are positively correlated with HIF2α protein levels in breast cancer and are associated with poor clinical outcomes in patients with breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…One gene downregulated by anti-PD-1 in obese tumors was laminin subunit beta-2 ( Lamb2 ) ( Figure S3C ). In line with downregulation of Lamb2 with anti-PD-1 in obese murine tumors, low LAMB2 protein expression was associated with greater overall survival in estrogen receptor (ER)-negative (ER−) tumors ( Ősz et al, 2020 ). In ER− tumors, median survival was 29 months in high expressers versus more than 3-fold longer at 100 months in low LAMB2 protein expressers ( Figure 3C , HR = 2.57, and log rank p = 0.65, n = 54 patients).…”
Section: Resultsmentioning
confidence: 84%
“…Hence, we explored associations with obesity-mediated factors that could influence antitumor immunosurveillance to identify putative biomarkers of anti-PD-1 efficacy, namely, the gut microbiome. Obesity affects the gut microbiome (Pierre et al, 2016;Aron-Wisnewsky et al, 2021;Newman et al, 2021). Microbiota, including bacteria and fungi, are increasingly tied to response to ICB or chemotherapy through unknown mechanisms, but recent work suggests mechanisms including microbially derived metabolite signaling on immune cells (Mager et al, 2020;Sipe et al, 2020;Simpson et al, 2021;Langan et al, 2018;Gopalakrishnan et al, 2018;Frankel et al, 2017;Vé tizou et al, 2015;Matson et al, 2018;Routy et al, 2018;Iida et al, 2013;Viaud et al, 2013;Sepich-Poore et al, 2021;Sivan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sources for the databases were GEO, EGA, and TCGA. It is a meta-analysis based discovery and validation of survival biomarkers 35 . We assessed the association between ORCs and overall survival(OS) in BC patients via Kaplan-Meier Plotter.…”
Section: Kaplan-meier Plotter (Km-plotter)mentioning
confidence: 99%